The Relationship Between Digital Competence and Facilities with Digital Efficacy of Lecturers in Teaching Engineering Subjects - Abdul Kamil, Amirah; Rozali, Mohd Zulfadli; Zeng Xiuzhen (Online Journal for TVET Practitioners, 2026)
Lecturers must not only be familiar with technology but also be proficient in applying digital tools in teaching. However, previous studies show that the knowledge level among engineering lecturers regarding Building Information Modelling (BIM) requires improvement in both awareness and competency in using this technology effectively. This deficiency in digital skills can negatively impact the overall effectiveness of teaching and learning (T&L), potentially leading to a decrease in lecturers' confidence and a subsequent reduction in the quality of education and student performance. This study aims to identify the level of digital competency and the facilities provided by the institution, as well as to assess the digital efficacy of lecturers using digital technology in teaching engineering subjects. Additionally, this study aims to identify the relationship between digital competency and the provided facilities with the digital efficacy of lecturers. This survey-based study uses a quantitative approach, and a total of 83 respondents provided feedback through a questionnaire. Descriptive analysis was used to identify the level of digital competency of lecturers, the level of facilities, and the digital efficacy of lecturers. Pearson correlation analysis was used to observe the relationship between digital competency and facilities with the digital efficacy of lecturers. The findings show that the level of digital competency of lecturers is high with a mean score of M=4.14 and SD=0.40, meaning they can effectively integrate digital resources into teaching strategies and use diverse channels to communicate with students. The level of facilities is also high with a mean score of M=4.12 and SD=0.54, indicating that the institution provides adequate infrastructure, such as digital systems and support staff, that successfully encourages technological use. Finally, the level of digital efficacy is high with a mean score of M=4.14 and SD=0.56, which translates to lecturers feeling comfortable and confident in their ability to provide immediate feedback and adapt to various digital teaching situations. The study findings from the Pearson correlation test show a significant relationship between digital competency and facilities with the digital efficacy of lecturers, with Pearson correlation coefficients of r=0.77 and r=0.71, respectively. In conclusion, engineering lecturers at the studied institution possess a high level of digital competency, which is crucial because it enables them to effectively integrate digital resources into teaching strategies and use diverse digital channels to collaborate with students and colleagues. Specifically, this mastery allows lecturers to foster innovative talent and utilize industry-standard tools like MATLAB to enhance the quality of engineering education. The implication of this study is that by fostering such competencies alongside adequate institutional facilities, universities can significantly enhance lecturers' digital efficacy, thereby ensuring a high-quality, resilient learning environment that meets the demands of the Fourth Industrial Revolution.